Resilience capacity, food consumption and socio-economic status in Zimbabwe - Conrad Murendo; Givious Sisito; Grown Chirongwe (Cogent Economics & Finance, 2023)
This article examined the role of resilience and resilience pillars on household food consumption differentiated by socio-economic status. The cross-sectional data of 2228 rural households came from Zimbabwe Poverty, Income, Consumption and Expenditure Survey and principal component analysis was used for computing resilience capacity. The study employed dietary diversity and food consumption as outcome variables. Negative binomial regression and linear regression are used for analysis. Resilience capacity improved household food consumption across all socio-economic classes, and effects are more pronounced among poorer households. The resilience pillars-assets (AST), access to basic services and adaptive capacity (AC)-improved household food consumption, while social safety nets (SSN) improved food consumption among the poor only. Public and private sectors and policy makers should consider promoting interventions that increase AC, AST and basic services across all socio-economic classes of households with special focus on poor households and low rainfall areas. SSN should continue to be efficiently targeted to poorer households.
Keywords: 330; food consumption; pillars; resilience capacity; shocks; socio-economic class; Zimbabwe